Prognostic Value and Immunological Role of MORF4-Related Gene-Binding Protein in Human Cancers - Chai, Dongqi; Zhang, Lilong; Guan, Yongjun; Yuan, Jingping; Li, Man; Wang, Weixing (Frontiers in Cell and Developmental Biology, 2021)
MORF4-related gene-binding protein (MRGBP) is the subunit of the NuA4 histone acetyltransferase complex which is involved in transcriptional activation of select genes principally by acetylation of nucleosomal histones H4 and H2A. Much of the research indicated an oncogenic role of MRGBP in the development of cancers. However, it is still unknown the role MRGBP plays in human cancers, which deserves further exploration. In this research, the expression profile, prognostic value of MRGBP, and the relationship between MRGBP and immune infiltration were explored in 33 types of cancer. The differences in MRGBP expression in tumor and normal tissues were explored using data from The Cancer Genome Atlas, Gene Expression Omnibus and ONCOMINE. Analysis of the association between MRGBP and prognosis using Kaplan-Meier survival curve and COX analysis. The data of Tumor mutational burden (TMB), microsatellite instability (MSI) from TCGA. The relationship Between MRGBP expression and immunity was analyzed using the ESTIMATE algorithm and CIBERSORT. Furthermore, we explored MRGBP expression and the relationship between MRGBP expression and macrophage infiltration using immunohistochemical analysis in lower grade glioma(LGG). Our results revealed that MRGBP was highly expressed in most cancer tissues compared with normal tissues. Tumors with increased MRGBP expression had a high clinicopathologic stage and poor prognosis. The expression of MRGBP was closely related to the TMB, MSI. We also found a significant negative correlation between MRGBP expression and stromal scores and immune scores in various types of cancer. Furthermore, MRGBP expression was associated with a variety of immune cells including B cells, NK cells, T cells, and macrophages. LGG was selected as a representative cancer type for further study, the results of immunohistochemistry indicated that the protein levels of MRGBP were significantly elevated in tumor tissues. Moreover, patients with high MRGBP expression were associated with short survival rates. MRGBP expression level was positively related to the number of infiltrating M0 macrophages. Immunohistochemistry confirmed that M0 macrophage infiltration in the MRGBP-high group significantly increased. In conclusion, these results reveal that MRGBP can serve as a potential prognostic biomarker and it plays an important role in tumor immune infiltration in various tumors, especially in LGG.